Rebirth of self and identity: an analysis of Meena Alexander’s Manhattan music - Krishnamoorthy, Ramesh; Krishnamurthy, B. (Penerbit Universiti Kebangsaan Malaysia, 2016)
This paper illustrates how Meena Alexander explores the prospect of outgrowing the sense of rootlessness of Asian immigrants in America in Manhattan Music. According to her it is managed by vocational and social engagements, and bonding with fellow expatriates. Alienation, search for identity and emotional insecurity of immigrants have hitherto been the dominant themes of diasporic literature. However, in the context of globalisation the concept of ‘home’ as a giver of emotional security cries for a redefinition. Meena Alexander’s Manhattan Music analyses the impact of transplantation from natal to post-marital space in the lives of women characters. Sandhya Rosenblum, Draupadi Dinkins, Sakhi and a few others despite the differences in their upbringing, experience the trauma of dislocation at first, but outgrow the same. Sandhya wrestles between her conflicting roles, a mother in New York and a daughter revisiting India, and in neither does she feel at home. But after her recovery from the shock of suicide, she escapes from racial thinking. It constitutes a rebirth of self for her. Similarly, Draupadi, the alter-ego of Sandhya, comes to realise being an American is only a part of her Self. Meena Alexander’s central vision in all her writings is the need of the immigrants for adapting themselves to the changed environment to find meaning in their lives. In Manhattan Music, the writer emphasises this idea by portraying Sandhya’s inner conflict in her adopted country at first and later her awakening to the truth that we all have several “homes” or as Homi Bhabha suggests we have to “desire for social solidarity: I am looking for the join…I want to join…I want to join.” (Bhabha 1994, p.18)